Eccentric training in patients with chronic Achilles tendinosis: normalised tendon structure and decreased thickness at follow up. Issue 1 (29th January 2004) - Öhberg, L; Lorentzon, R; Alfredson, H
Abstract : Objective: To prospectively investigate tendon thickness and tendon structure by ultrasonography in patients treated with eccentric calf muscle training for painful chronic Achilles tendinosis located at the 2–6 cm level in the tendon. Methods: The patients were examined with grey scale ultrasonography before and 3.8 years (mean) after the 12 week eccentric training regimen. At follow up, a questionnaire assessed present activity level and satisfaction with treatment. Results: Twenty six tendons in twenty five patients (19 men and six women) with a mean age of 50 years were followed for a mean of 3.8 years (range 1.6–7.75). All patients had a long duration of painful symptoms (mean 17.1 months) from chronic Achilles tendinosis before treatment. At follow up, 22 of 25 patients were satisfied with treatment and active in Achilles tendon loading activities at the desired level. Ultrasonography showed that tendon thickness (at the widest part) had decreased significantly (p<0.005) after treatment (7.6 (2.3) v 8.8 (3) mm; mean (SD)). In untreated normal tendons, there was no significant difference in thickness after treatment (5.3 (1.3) mm before and 5.9 (0.8) mm after). All tendons with tendinosis had structural abnormalities (hypoechoic areas and irregular structure) before the start of treatment. After treatment, the structure was normal in 19 of the 26 tendons. Six of the seven patients with remaining structural abnormalities experienced pain in the tendon during loading. Conclusions: Ultrasonographic follow up of patients with mid-portion painful chronic Achilles tendinosis treated with eccentric calf muscle training showed a localised decrease in tendon thickness and a normalised tendon structure in most patients. Remaining structural tendon abnormalities seemed to be associated with residual pain in the tendon.